Pengaruh Model Problem Based Learning Berbantuan Media Audio Visual YouTube Terhadap Kemampuan Berpikir Kritis Siswa: Penelitian Eksperimen - Ilyas, Muh; Aeni Rahman, Syarifa; Hakim, Ulfayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low critical thinking skills of students in social studies learning caused by the use of conventional learning methods that do not actively involve students. This study aims to determine the effect of the Problem-Based Learning model assisted by YouTube audio-visual media on the critical thinking skills of fourth-grade students at SDI Parangkangtisang, Gowa Regency. This study used a quantitative approach with an experimental type and a One Group Pretest-Posttest Design. The research sample consisted of 19 students. Data collection techniques used tests and observations, while data analysis included descriptive and inferential statistics. The results showed an increase in students' critical thinking skills after the implementation of the learning model. Teacher and student activity during learning increased at each meeting, indicating that the learning process was running well. The results of the data analysis showed a significant difference between the results before and after the treatment, and the level of improvement was categorized as high. This proves that the Problem-Based Learning model assisted by YouTube audio-visual media is effective in improving students' critical thinking skills. The conclusion of this study indicates that the implementation of the problem-based learning model supported by audio-visual media can optimally improve the quality of learning and student engagement.